Role of Adaptive Re-use of Buildings in the Revitalization Process of the Historic Quarters: The Case of the Walled City of Famagusta - Rahbarianyazd, Rokhsaneh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
At some point in its lifespan, every building will lose the purpose for which it was built and may become obsolete in terms of its function. These obsolete buildings will have a negative effect on both the character of buildings and the area, in which they are located. Adaptive reuse, which is adaptation of this kind of building to a new function or use, on a large scale can create a new confidence through a deliberate functional diversification and/or restructuring and promote revitalization of the historic urban quarters. This action gives an impulse to both the building and its environment. Warehouses, which are located in the historic Walled City of Famagusta, with good and improving access and connectivity, with their large floor area, high ceilings, strong floor which would play a significant role in the revitalization of the historic area, became vacant or are under-utilized, due to various reasons. Depending on certain conditions, as any type of building the Warehouses can also adapt to a new function which can be referred to the most appropriate reuse. In the Revitalization Plan of the Walled City of Famagusta, which has been prepared by the Famagusta Municipality in 2005, these warehouses have been considered as the robust and suitable buildings for conversion to various alternative uses to promote the area; thus, some alternative reuse were proposed for them. In this thesis all of these proposals have been re-evaluated according to six criteria in order to determine the most appropriate reuse for these warehouses. Keywords: Revitalization, Historic Quarters, Adaptive Reuse, Industrial buildings+ Warehouses, Walled City of Famagusta.

ÖZ: Her bina kendi yaşam sürecinde amacını ve fonksiyonunu kaybedip terkedilebilir. Terkedilen binaların kendilerine ve çevrelerine olumsuz etkileri vardır. Yeniden kullanım, binalara yeni fonksiyon veren veya yeniden kullanımını sağlayan işlev, büyük ölçekte fonksiyonel çeşitlilik ve/veya yeniden yapılandırma sağlayarak tarihi kentsel alanların canlandırılmasını sağlar. Bu eylem, bina ve içinde bulunduğu çevreye önemli bir katkı sağlar. Gazimağusa Sur-içinde yer alan depo binaları, kolay ulaşımı, geniş alan, yüksek tavan, güçlü zemin gibi özellikleri ile, tarihi alanın bölgelerinin yeniden tanıtılmasını sağlar. Yapılan yeniden kullanım işlevi binaya ve anlandırılmasında önemli rol oynama potansiyeline rağmen, çeşitli nedenlerden dolayı boş yada atıl durumdadırlar. Belirli koşullara bağlı olarak, diğer binalar gibi,depo binalarının da türüne uygun olarak yeni bir fonksiyon verilebilir. 2005 yılında hazırlanan Gazimağusa Suriçi Canlandırma Projesi kapsamında, endüstriyel ambarlar, bölgenin canlandırılmasında çeşitli alternatif kullanımlar için güçlü ve uygun olarak belirlenmişlerdir. Bu nedenle bazı alternatif yeniden kullanım fonksiyonları depo binaları için önerilmiştir. Bu tezde en uygun yeniden kullanımı belirlemek için, tüm öneriler altı kritere göre yeniden değerlendirilmiştir. Anahtar Kelimeler: yeniden canlandırma, tarihi bölge, yeniden kullanım, endüstriyel yapılar+ depo binaları, Mağusa Surlariçi.
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2014. Supervisor: Prof. Dr. Naciye Doratlı.
Keywords: Architecture; Historic buildings - Sustainability - Conservation and restoration - Famagusta (Cyprus, North); Historic Urban Quarters - Revitalization- Famagusta (Cyprus, North); Historic Buildings - Preservation and Re - Use; Revitalization; Historic Quarters; Adaptive Reuse; Industrial buildings+ Warehouses; Walled City of Famagusta